INTENSIFIKASI MAKROPROPAGASI TANAMAN PISANG DALAM UPAYA PEMBERDAYAAN KARANG TARUNA CENTRAL KECAMATAN PATRANG JEMBER - Agung Nugroho Puspito; Mellfani Rhamadinda Nendra Tigara; Mohammad Ubaidillah (Jurnal Hasil Pengabdian kepada Masyarakat Universitas Jember, 2022)
Increasing community empowerment and self-help needs to be considered in order to achieve social independence and increase the village economy evenly. Plant propagation is important in meeting the seed needs of rural communities. The role of universities as institutions of higher education and research development must be able to be the first hand in overcoming all aspects of society. The Faculty of Agriculture, University of Jember, has developed many macropropagation techniques for various crops, including food, horticulture, ornamentals and plantations. Various research and scientific development results have not been fully applied to the community. The problem of banana cultivation in Patrang Village is still using the traditional way. The use of conventional seeds is often not standardized for good quality, which will have a major impact on the declining yield of horticultural crops. The purpose of this program is to provide knowledge to the people of Patrang Village in the form of explanations of banana plant macropropagation techniques through workshops, training, and direct assistance. Provision of seeds is important in plant cultivation and must have good quality. Macropropagation technique is one way to get quality seeds that have superior properties, free of disease, and high viability. Macropropagation technique is able to produce more quantity of vegetative seeds, able to maintain the same character as the parent and the waiting time to bear fruit is faster. The intensification of macropropagation of banana plants is expected to increase community empowerment and self-help of banana seedlings in Patrang Village, Patrang District, Jember Regency.